DETERMINAÇÃO DE ÁCIDO LIPÓICO SOBRE ELETRODO DE GRAFITE PIROLÍTICO MODIFICADO COM FTALOCIANINA DE COBALTO - Ferreira, Ana Paula Mota (2012)
Lipoic acid, also known as thioctic acid is a compound organosulfur derived from octanoic acid, which is a saturated fatty acid. It is an antioxidant that has the property of suppressing free radicals in both aqueous and lipid environment, which differs from other antioxidants. Nowadays, various techniques are employed for determining the lipoic acid such as capillary electrophoresis, chromatography, high performance liquid chromatography efficiency. However, the electrochemical detection is a promising method, because since it is less labor intensive and can distinguish between the oxidized and reduced form of lipoic acid. A growing number of studies has shown the need for a rapid procedure for evaluating the content of lipoic acid and electrochemical techniques were employed successfully. This study aimed to develop a pyrolytic graphite electrode modified with cobalt metallophthalocyanines for the determination of lipoic acid. The oxidation of lipoic acid has a peak located at approximately 0.8 V vs SCE, being close to the peak potential presented in the literature. The cyclic voltammograms reported in the presence of 1 x 10-3 mol L-1 of lipoic acid in phosphate buffer 0.1 mol L-1 (pH 7.0) to a potential scan rate 25 mV s-1 showed that the electrode modified with 1 x 10-4 mol L-1 CoPc, showed better profiles in relation to the voltammetric electrode unmodified or modified with other metallophthalocyanine. Is then optimized the parameters for the cyclic voltammetry, chronoamperometry and differential pulse. Was then constructed curves for analytical techniques mentioned. For the cyclic voltammetry technique limits of detection and quantification are 8.7 × 10-8 mol L-1 and 2.9 x10-7 mol L-1 for the technique of chronoamperometry 9.8 x 10-8 mol L-1 and 3.2 x 10-7 mol L-1 and differential pulse voltammetry are 3.4 x 10-9 mol L-1 and 1.2 x 10-8 mol L-1 respectively.